Medical radiation exposure of patients in the United States : recommendations of the National Council on Radiation Protection and Measurements. (National Council on Radiation Protection and Measurements, 2019)
"This Report is an update 10 y after the publication of NCRP Report No. 160 (NCRP 2009) and is focused on 2016 doses to patients from medical exposures. Occupational doses and doses to caregivers are not included. Discussion of any potential risks and benefits of the use of medical exposures was beyond NCRP's scope of work. Several metrics are estimated as follows: number and type of procedures involving patient diagnostic and interventional medical radiation procedures; effective dose per procedure which is a calculated dose based upon the type of radiation and the radiation detriment (associated primarily with the induction of cancer) in tissues exposed (risk factors are based on average population characteristics and derive from linear nonthreshold assumptions); collective effective dose which is the number of procedures multiplied by the effective dose per procedure; and annual average individual effective dose which is the collective effective dose divided by the U.S. population, whether the persons were exposed or not, and allows comparison of the magnitude of medical radiation exposure to that from various nonmedical sources"-- Provided by publisher.
Keywords: Ionizing radiation -- Dosage -- United States.; Ionizing radiation -- Environmental aspects -- United States.; Health risk assessment -- United States.; Ionizing radiation -- Physiological effect.; elektronické knihy; electronic books